Cultural Adaptation and Reliability of the Compliance with Standard Precautions Scale (CSPS) for Nurses in Brazil - Pereira, Fernanda Maria Vieira (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2017)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: this study aimed to carry of the cultural adaptation and to evaluate the reliability of the Compliance with Standard Precautions Scale (CSPS) for nurses in Brazil. METHOD: the adaptation process entailed translation, consensus among judges, back-translation, semantic validation and pretest. The reliability was evaluated by internal consistency (Cronbach alpha) and stability (test-retest). The instrument was administered to a sample group of 300 nurses who worked in a large hospital located in the city of São Paulo/SP, Brazil. RESULTS: through the semantic validation, the items from the scale were considered understandable and deemed important for the nurse´s clinical practice. The CSPS Brazilian Portuguese version (CSPS-PB) revealed excellent interpretability. The Cronbach`s alpha was 0.61 and the intraclass correlation coefficient was 0.85. CONCLUSION: the initial study showed that CSPS-PB is appropriate to assess compliance with standard precautions among nurses in Brazil. The reliability was considered acceptable. Furhter study is necessary to evaluate its comprehensive psychometric properties.